Analysis of Syntactic Language Errors in the Field of Syntax on the Online News Portal Isknews.com January 2024 Edition as Feasibility of Teaching Materials Critical Reading for Grade XI High School Students - Malika Uswatun Hasanah; Atria Windi Syarifah; Nayla Syarifa; Primastuti Nugraheni; Nukti Wahyu Ilhami; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Qurrota Ayu Neina; Amilia Buana Dewi Islamy (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This research analyzes the news text on the ISKNEWS.COM online news portal. Then the other purpose of this research is to prove that the news texts in the portal, after being analyzed, are worthy of being used as teaching materials for critical reading for grade XI high school students. This research uses a descriptive qualitative approach and a syntactic approach as the theoretical approach. The writer obtained data by reading several related references and recording information that could be used as data. For this reason, reading and scanning techniques were used in this research. The data in this study are news texts from the January 2024 edition of the ISKNEWS.COM online news portal. The data analysis method used is the agih method. The writer analyzes the text by identifying sentences that do not follow the syntax rules and the feasibility of the text as a good and correct news text. The analysis results show several syntactic errors identified, namely sentences with non-standard structures, the use of absorbed words in sentences, ambiguous sentences, inappropriate diction in sentence formation, and the use of words inefficiently. In addition, the news puzzle is proven to be used as teaching material for critical reading for grade XI high school students. This is because the syntactic errors found are still tolerable, and the text has a good structure.